Near field enhancement in Ag Au nanospheres heterodimers - Encina, Ezequiel Roberto (2011)
The near field enhancement in Ag Au nanospheres heterodimers excited at their respective resonance wavelengths is studied in detail using rigorous electrodynamics calculations based on the Generalized Multiparticle Mie theory. The effect of incident polarization, nanosphere radius, and interparticle separation on the distribution pattern and magnitude of the near field enhancement is analyzed. As in the homodimer case, the highest enhancement values are found for incident polarization parallel to the dimer axis. However, there are significant different enhancement patterns around the dimer according to the excitation wavelength. Analyzing the vector field plot of the enhancement, and comparing it with those corresponding to Ag and Au nanospheres homodimers, the differences observed are rationalized in terms of multipole excitations to explain the effect of breaking the symmetry of the plasmonic heterodimer. The results presented could be a useful tool for future design and engineering of plasmonic devices based on the near field properties such as substrates for enhanced spectroscopies and sensing. © 2011 American Chemical Society.